Sexually Transmitted Infections - LE Nicolle (Canadian Journal of Infectious Diseases and Medical Microbiology)
Sexually transmitted infections (STIs) other than HIV have reappeared as an important public health problem in developed countries (1). In the late 1970s and early 1980s, research and treatment of the 'classic' STIs - gonorrhea, syphilis and chlamydia - were a major focus of infectious diseases practice and research. There were large outbreaks of syphilis in parts of Canada (2), penicillin-resistant Neisseria gonorrhoeae was a concern (3), and high rates of Chlamydia trachomatis infection with complications of pelvic inflammatory disease and ectopic pregnancy were being reported (4,5). Then, HIV infection emerged, with its spectre of a wasting, early death. There was no effective treatment, and safe sexual practices were embraced and adhered to by high-risk populations as the only effective way to avoid infection. These practices effectively prevented other STIs; rates of syphilis, gonorrhea and chlamydia infection plummeted in developed countries (5). For at least a decade, it appeared that HIV might be an end to all STIs, at least for some parts of the world. STIs continued unabated in developing countries, as many epidemiological and therapeutic studies explored the association of STIs with HIV infection.